Influence of BG-11 culture media on growth of Cyanobacteria, Oscillatoria Species - Yadav, A.; Dubey, K.; Parveen, S.; Rout, S.; Singh, D. (IJRDO-Journal of Applied Science, 2016)
Oscillatoria species is a Cyanobacteria that is important because it can conduct photosynthetic activities. it has a long un branching filamentous morphology and is green colour due to the chlorophyll content which is the unique features that set it apart from other. In this investigation it was cultured on BG-11 media and influences the growth after 1st week, parameters recorded i.e., fresh weight (2.04g) and dry weight (0.08 g) at room temperature. On 4th week fresh weight (at room temperature) recorded (1.18 g) and dry weight (0.1g). Culturing of Cyanobactria, Oscillatoria species is the part of biotechnolgy but they play a very important role in all the field of environmental science and biology.